2017
DOI: 10.1128/aem.03386-16
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Acetone/Butanol Ratio during Fermentation of Corn Stover-Derived Hydrolysate by Clostridium beijerinckii Strain NCIMB 8052

Abstract: Producing biobutanol from lignocellulosic biomass has shown promise to ultimately reduce greenhouse gases and alleviate the global energy crisis. However, because of the recalcitrance of a lignocellulosic biomass, a pretreatment of the substrate is needed which in many cases releases soluble lignin compounds (SLCs), which inhibit growth of butanol-producing clostridia. In this study, we found that SLCs changed the acetone/butanol ratio (A/B ratio) during butanol fermentation. The typical A/B molar ratio during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 55 publications
(77 reference statements)
0
9
0
Order By: Relevance
“…The characteristics of this experimental design are shown in Table A1. The nutrients and their concentration ranges were selected according to literature data (Liu et al, 2017;Qureshi and Blaschek, 1999;Qureshi et al, 2014;Ujor et al, 2016).…”
Section: Optimisation Of Fermentation Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of this experimental design are shown in Table A1. The nutrients and their concentration ranges were selected according to literature data (Liu et al, 2017;Qureshi and Blaschek, 1999;Qureshi et al, 2014;Ujor et al, 2016).…”
Section: Optimisation Of Fermentation Conditionsmentioning
confidence: 99%
“…In addition, polymeric resins potentiate the reduction of the overall production cost due to their reusability without affecting the process efficiency and in some cases without altering the sugar concentration contained in the hydrolysate (Gao and Rehmann, 2016). Previous studies on biobutanol production from corn stover have tried to solve each one of the abovementioned parameters through the selection of mutant and wild type solventogenic Clostridium strains (Liu et al, 2017;Qureshi et al, 2010;Tang et al, 2017;Wang and Chen, 2011;Xue et al, 2016a;Zhang et al, 2018); the use of different pretreatment reagents and conditions (Baral and Shah, 2017;Tang et al, 2017;Xue et al, 2016a;Zhang et al, 2014) and hydrolysate detoxification by various methods (Liu et al, 2017;Qureshi et al, 2010;Tang et al, 2017;Wang and Chen, 2011;Xue et al, 2016a;Zhang et al, 2018). Currently, studies conducted to potentiate biobutanol industrial production from corn stover are clearly required to increase yield values, but also to reduce the associated economic costs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To release the inhibition of ABE fermentation, several detoxification methods have been developed. The over-liming method is an effective way to reduce the inhibition of ABE fermentation from lignocellulose hydrolysate (Liu et al 2017 ). Mutant strains with higher inhibitor tolerances have also been obtained by mutagenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive studies on the responses of Clostridium strains in the Ca 2+ -containing real biomass hydrolysate, especially at molecular levels, are still very limited. Liu et al found that overliming removed the growth inhibitory effect of corn stover hydrolysate but was unable to eliminate the effects of soluble lignin compounds (SLC) on redox balance in C. beijerinckii , leading to a high acetone/butanol ratio 18 . It was also reported that thioredoxin reductase gene, trxB , was up-regulated in the late exponential phase, possibly to response to the increased oxidative stress caused by SLC 18 .…”
Section: Introductionmentioning
confidence: 99%